A CLINICAL STUDY ON THE EFFECT OF PUNARNAVADI CHURNA, SINGHANADA GUGGULU IN THE MANAGEMENT OF AMAVATA (RHEUMATIOD ARTHRITIS) - Rohit, Ranjan; Singh, Mahendra; Richa, Singh; Kavitha, M.; Shardul Vikram, Singh (International Journal of Ayurveda and Pharma Research, 2015)
Amavata, is firstly introduced as an independent disease in Madhav Nidana. It is a disease of Madhyam roga marga as it affects Sandhi and Hridya marma. Though Ama and Vata are the two main predominant pathogenic factors but the disease also represents Tridoshic vitiation. The affliction of joints by Vata dosha in association with Ama shows that both play equal role of Dosha and Dushya in the causation of this disease. This study includes evaluate the effect of Trial drugs Punarnavadi churna with Anupana of Rasna Saptak Qwatha and Eranda taila on the signs and symptoms of Amavata and also to evaluate the effect of trial drug with a standard drug Singhanada Guggulu on the signs and symptoms of Amavata. In short we can say that, Amavata is the resultant of improper digestion or partially digestion of the food particles due to hypofunction of Gatharagni and also due to accumulation of mala in the body and it is also considered as Pratham doshadusti. It may be considered as partially or incomplete metabolized Dathu in case of Dhatvagni mandata. This study might be helpful in breakdown Samprapti of Amavata roga and give right way to patient of Amavata.